Urinary Tract Infections in Men in Primary Care in Catalonia, Spain - Silvia Fernández-García; Ana Moragas Moreno; Maria Giner-Soriano; Rosa Morros; Dan Ouchi; Ana García-Sangenís; Mònica Monteagudo; Ramon Monfà; Carl Llor (MDPI AG, 2023)
Antimicrobial resistance is a major global problem that is primarily driven by the excessive and inappropriate utilization of antibiotics. Urinary tract infections (UTIs) are frequent in primary health care (PHC) and are typically treated with antibiotics. There is ample evidence on the management of this condition in women but not in men. The aim of this study was to describe the epidemiology of UTIs in men in Catalonia, Spain. We conducted a population-based observational cohort study that included male patients diagnosed with UTI within our SIDIAP and CMBD database during the period from 2012 to 2021. UTI diagnoses were grouped into five main groups (cystitis, prostatitis, orchitis and epididymitis, urethritis, and pyelonephritis). Of the 316,762 men with at least one recorded UTI episode, the majority were registered with a diagnosis of cystitis in PHC (212,958 patients). Quinolones were the most commonly recorded treatment for UTIs (between 18.3% and 38.6%, depending on the group), except for urethritis in which a combination of antibiotics (36.7%) was most frequently used. The treatment duration period was between 9 days and 18 days, except for the prostatitis group, in which treatment was extended to 21 days. Urine cultures were documented in up to 30% in the cystitis group. Pyelonephritis was the category linked to most septicemia cases (3.0%). Conclusions: This is the first study to assess UTIs in men using a large PHC database in Spain. The sociodemographic characteristics of our sample are similar to other studies in the literature. In our setting, the use of quinolones for the treatment of UTIs is the most registered, and its duration was between 9 days and 18 days, despite the fact that resistance to quinolones exceeds 20% of the strains in our area.